2014
DOI: 10.1021/jp505661e
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a Rare Earth Ion–Extractant Complex Arrested at the Oil–Water Interface During Solvent Extraction

Abstract: Selective extraction of metal ions from a complex aqueous mixture into an organic phase is used to separate toxic or radioactive metals from polluted environments and nuclear waste, as well as to produce industrially relevant metals, such as rare earth ions. Selectivity arises from the choice of an extractant amphiphile, dissolved in the organic phase, which interacts preferentially with the target metal ion. The extractant-mediated process of ion transport from an aqueous to an organic phase takes place at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
124
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(129 citation statements)
references
References 37 publications
(68 reference statements)
5
124
0
Order By: Relevance
“…Solvent extraction has been widely employed for the separation of metals such as Cu, Ni, Co, and rare earth elements, as well as in the field of nuclear fuel technology like actinide recovery and purification, radionuclide production [7,8,9]. It is basically composed to mixing for extraction, settling and stripping procedure in each stage.…”
Section: Introductionmentioning
confidence: 99%
“…Solvent extraction has been widely employed for the separation of metals such as Cu, Ni, Co, and rare earth elements, as well as in the field of nuclear fuel technology like actinide recovery and purification, radionuclide production [7,8,9]. It is basically composed to mixing for extraction, settling and stripping procedure in each stage.…”
Section: Introductionmentioning
confidence: 99%
“…The same temperature protocol was used for these experiments on SrCl 2 to facilitate comparison with the earlier experiments on ErCl 3 . 9 To ensure that X-rays probe the high density phase of DHDP at the dodecane−water interface, the experimental temperature T X-ray was typically 5−8°C below the transition temperature T o for each sample. Figure 5a illustrates X-ray reflectivity normalized to the Fresnel reflectivity, R/R F , from interfaces between 10 −4 M DHDP in dodecane and 10 −5 M SrCl 2 in water for all values of pH studied.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The electron density ρ 1 in the head group is due to a combination of water molecules, Sr 2+ ions, phosphate head group (PO 4 ) of DHDP, which may be protonated at lower pH (see Chart 1). Assuming that there is no unoccupied volume in slab 1, the total number of electrons in slab 1 is given by 8) and the volume of slab 1 is 9) where N j is the number of each species per DHDP molecule in slab 1 (N PO 4 = 1). …”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the attenuation of incident and fluorescence radiation by the liquid media and the requirement of horizontal sample geometries pose limitations to the fluorescence detection efficiency. Only recently, Bu et al reported the quantification by XSW fluorescence under total reflection of heavy ion amounts immobilized at oil/water interfaces via extractant molecules [64,65]. Their measurement configuration corresponds to Fig.…”
Section: Liquid/liquid Interfacesmentioning
confidence: 99%